SITUATIONAL LEADERSHIP AND ACHIEVEMENT MOTIVATION TO EMPLOYEE JOB SATISFACTION AT NURUS SALAM DELITUA FOUNDATION - Syamsuri, Abd. Rasyid; Arianti, Andini; Audina, Ika; Prabowo, Dhiken; Situmorang, Havia Maysarah (Jurnal Bisnis Mahasiswa, 2022)
At the Nurus Salam Foundation, Hamlet VI, Mekar Sari Village, Delitua District, this study will l analysis at the impact of situational leadership and achievement motivation on employee job satisfaction. This type of study uses descriptive quantitative research tools, observation data gathering techniques, and questionnaires. A total of 43 employees were included in this investigation. The sampling strategy employed in this study was saturation sampling, which entails taking a sample from the entire population. The multiple linear regression method was employed with the SPSS application as the analytical method. The partial test findings suggest that the leadership variable (X1) has a t-value of (0.079) < (2.022), indicating that it has a positive but insignificant effect on job satisfaction (Y). The accomplishment motivation variable (X2) has a value of t count (3,098) > (2,022), indicating that it has a positive and substantial effect on Job Satisf`action (Y). According to the findings of the simultaneous test, the estimated f value is 4.820 > f table 2.84, with a significant value of 0.013 < 0.05, indicating that situational leadership (X1) and achievement motivation (X2) have a positive and substantial effect on job satisfaction (Y)